1999
DOI: 10.4148/2378-5977.1869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interseeding legumes into endophyte-infected tall fescue pastures on forage production and steer performance (1999)

Abstract: SummaryA total of 135 steers grazed high-endophyte tall fescue pasture interseeded with either lespedeza, red clover, or ladino clover during 1995, 1996, and 1997. Legume cover, forage dry matter production, grazing steer performance, and subsequent feedlot performance were measured. Legume treatment caused no differences in forage availability. Grazing gains corresponded to the amount of legume coverage present. Results of this study indicate that interseeding high endophyte fescue pastures with ladino clove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Red clover went from 5% of the total biomass in 2009 to 3% in 2010 and then 2% in 2011. Lomas et al (1999) also found that when red clover was drilled into tall fescue pastures, it started at 5% of pasture composition and, by year three, was 2% of composition. Finding significant white clover biomass in 2011, 3 yr after planting, was somewhat surprising.…”
Section: Discussionmentioning
confidence: 91%
“…Red clover went from 5% of the total biomass in 2009 to 3% in 2010 and then 2% in 2011. Lomas et al (1999) also found that when red clover was drilled into tall fescue pastures, it started at 5% of pasture composition and, by year three, was 2% of composition. Finding significant white clover biomass in 2011, 3 yr after planting, was somewhat surprising.…”
Section: Discussionmentioning
confidence: 91%
“…It is a major component in many cool‐season pastures in southeast Kansas, and it set seed each autumn to potentially re‐establish itself the next year in western Kansas. However, the frequency of lespedeza declined each successive year and did not contribute to overall yield or quality, whereas in southeast Kansas, Korean lespedeza is able to contribute significantly to forage production (Posler & Fransen, 1982; Lomas et al., 1999) and steer performance (Lomas et al., 1999) on grass–legume stands in successive years. As long as the grazing management allows it to rest in late summer, or if the plants are allowed to flower and set seed without heavy defoliation, Korean lespedeza should be able to produce seed annually to maintain stands.…”
Section: Discussionmentioning
confidence: 99%
“…In this region, producers can plant cool-season annuals such as winter wheat (Triticum aestivum L.) in September or early October with growth of these varieties extending from November to May (Hoveland et al, 1991). Total gains and average daily gain for cattle grazing annual cool-season forages in the winter have been found to exceed average daily gains of cattle grazed on tall fescue over the same time period (Hoveland et al, 1991;Lomas, Moyer, and Kilgore, 1999). Warm-season grasses, on the other hand, grow from late May through midsummer with fall dormancy starting in early October (Moore et al, 2004).…”
Section: Introductionmentioning
confidence: 99%